Controls on subduction reorganization in the Hellenic margin, eastern Mediterranean - Capitanio, F. A.; Zlotnik, S.; Faccenna, C. (Geophysical research letters, 2010)
In subduction modeling, interactions between the down‐going slab and neighboring plates are often neglected. Here, we have modeled the interactions between a subducting and an upper plate and show that, in such a system, subducting plate advance towards the stationary margin accommodates convergence. When interactions with the lower mantle are included in this system, deeper penetration of the slab allows transient increases in subduction rates and weakening in the upper plate. However this does not last long enough to mobilize the trench away from the upper plate. The constraints imposed by the convergence of major plates are more effective in reorganizing the tectonic style, by hampering, or even locking, the subducting plate motions resulting in sustained rollback and back‐arc opening over large time periods. A comparison with the tectonics of the Hellenic margin suggests that such boundary conditions might be the key to the reorganization of plate motions in this area.